Determinants of Successful Smoking Cessation in Surakarta - Joko Tri Atmodjo; RB. Soemanto; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2017)
Background: Smoking cessation is not an easy endeavor as tobacco addiction is a group of behavioral, cognitive and physiological phenomena. This study aimed to analyze the determinants of successful smoking cessation using health belief model (HBM), PRECEDE-PROCEED model, and theory of planned behavior (TPB).Subjects and Method: This was an analytic observational study with cross-sectional design. It was conducted in Surakarta, in December 2017. A sample of 165 study subjects consisting of 68 ex-smokers who were successful in smoking cessation and 97 smokers who were unsuccessful in smoking cessation, by snowball sampling. The dependent variable was smoking cessation. The independent variables were intention to quit smoking, attitude toward smoking cessation, outcome expectation, addiction, stress, perceived behavioral control (PBC), subjective norm, social support, family income, purchasing power, smoking duration, and access to cigarette. The data were collected using questionnaire and analyzed using path analysis.Results: Successful smoking cessation was directly affected by strong intention (b= 2.39, SE= 0.51, p <0.001), duration of smoking (≥10 years) (b= -3.46; SE= 0.57; p <0.001), and easy access to cigarettes (b= -1.28; SE= 0.52; p= 0.008). Intention is was affeced by positive attitude (b = 0.79, SE= 0.39, p= 0.046), positive PBC (b= 1.89, SE= 0.40; p<0.001), high purchasing power (b= -1.23; SE= 0.39; p= 0.002), and positive subjective norm (b= 1.38; SE= 0.40; p= 0.001). Positive PBC was affected by duration of smoking (≥10 years) (b= -2.32; SE= 0.47; p<0.001), positive outcome expectation (b= 1.04; SE= 0.49; p= 0.035), and addiction (b= -2.96; SE= 0.49; p<0.001). Positive attitude was affected by positive expectation outcomes (b= 1.09; SE= 0.34; p= 0.001). Positive subjective norm (b= 0.77; SE = 0.33; p= 0.020) and positive outcome expectation (b= 0.77; SE= 0.33; p= 0.020) were affected by social support. Smoking duration was affected by stress (b= 0.09; SE=- 0.04; p= 0.018). Cigarette purchasing power was affected by high income (b=2.78; SE= 1.43; p= 0.053).Conclusion: Successful smoking cessation is directly affected by intention, smoking duration, stress, and access to cigarette. Success smoking cessation is indirectly affected by attitude, addiction, PBC, subjective norm, social support, outcome expectation, family income, purchasing power.Keyword: smoking cessation, HBM, PRECEDE-PROCEED, TPBCorrespondence: Joko Tri Atmojo. School of Health Sciences Mamba'ul 'Ulum, Surakarta, Jl. Ring Road Utara, Tawangsari, Mojosongo, Jebres, Surakarta, Central Java. Email: jokotriatmojo1@gmail.com. Mobile: 081393319000.Journal of Health Promotion and Behavior (2017), 2(4): 332-344https://doi.org/10.26911/thejhpb.2017.02.04.05